EFEITO DE EXTRATOS DE MELIÁCEAS SOBRE Polyphagotarsonemus latus BANKS (ACARI: TARSONEMIDAE) - DE MELO, Thalia Mayara; VIEIRA, Gustavo Haralampidou da Costa; SILVA, Eliamara Marques (ANAIS DO ENIC, 2018)
-